RANCANG BANGUN PROTOTYPE TURBIN KAPLAN SKALA PLTMH - Andi Kusumayana B, Made; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
PLTMH is a type of generator that utilizes water resources for its workings. Utilization of water resources is still minimally carried out by the community, especially by students of Electrical Engineering at Udayana University because it must be implemented directly on a large enough river flow so that it is difficult to study. So, in this study, a prototype modeling of MHP using a Kaplan turbine was designed which is useful for the learning process before being implemented directly in the river. The Kaplan turbine prototype is designed with a head of 2 m, an input pipe of 2xdimxand a discharge of 12 L/s, has a total of 30 guide blades,xwith an opening angle of 30o, with a lengthxofx0.05 meters, a widthxof 0.045 meters, an inside diameterxofx0.33 metersxandxan outerxdiameterxofx0.42 meters. Thisxprototype has a total of 5 driving blades, withxanxouter diameterxofx0.16xmeters, a shaft neck diameterxof 0.06 meters, xaxrunner width ofx0.05 meters. The resultsxofxthe Kaplan turbine prototype test are able to produce axpowerxof 3.64xwatts, a torquexofx0.231xNm, andxanxefficiencyxof 1.54%.